Kirklin/Barratt-Boyes cardiac surgery morphology, diagnostic criteria, natural history, techniques, results, and indications - Kirklin, John W. (John Webster); Kouchoukos, Nicholas T. (Elsevier/Saunders, 2013)
Provides answers on various aspects of adult and pediatric cardiac surgery. This title covers the range of classic surgical procedures - including the alternate and minimally invasive surgical techniques - and presents the clinical evidence you need to make effective management decisions.